Penerapan Model Pembelajaran Explicit Instruction Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas IV SD GMIM Wailan - Norma N. Monigir (Peneliti.net, 2022)
This study aims to improve student learning outcomes in Indonesian language learning in grade IV GMIM Wailan Elementary School by using the Explicit Instruction learning model. This research used classroom action research method (PTK) which consists of four stages, namely: planning, action implementation, observation, and reflection which was carried out with two cycles. The research subjects were fourth grade students of GMIM Wailan Elementary School, with a total of 16 students, 12 male students and 4 female students. Data collection techniques are observation sheets and tests. The analysis technique used is percentage. The results of the research in cycle I the percentage of achievement was only 60.31% so that it was continued with research in cycle II. In the implementation of cycle II with efforts to improve learning from things that have not been achieved in cycle I, so that the achievement in cycle II is 84.37%. The conclusion of this study is that by applying the Explicit Instruction learning model can improve Indonesian language learning outcomes in grade IV GMIM Wailan Elementary School, especially in the material of writing personal letters to peers. Based on the conclusion, it is suggested as a teacher, to be able to use the Explicit Instruction learning model so that learning is more interesting, students are more active and creative, and stimulate